Intensity, intent, and ambiguity: Appraisals of workplace ostracism and coping responses. Issue 2 (21st November 2022) - Meral, Erdem O.; Vranjes, Ivana; van Osch, Yvette; Ren, Dongning; van Dijk, Eric; van Beest, Ilja
Abstract: Using both correlational and experimental designs across four studies ( N = 1251 working individuals), the current project aimed to contribute to the understanding of workplace ostracism by studying two research questions. First, we tested whether the subjective experience of targets reflects the current theorizing of ostracism. Second, drawing from the transactional theory of stress and coping, we investigated whether this subjective experience impacts targets' coping responses. Findings based on exploratory and confirmatory factor analyses supported the current theorizing of workplace ostracism such that perceived intensity, intent, and ambiguity were reflected in how targets appraised being ostracized at work. The appraisals were also related to coping responses. Perceived intensity predicted more approach‐oriented (e.g., confrontation) and less avoidance‐oriented coping responses (e.g., minimization). While attributions of intent also predicted some coping responses (e.g., instrumental support seeking), the explanatory power of perceived ambiguity was lower than the other two appraisals. Although these researcher‐defined dimensions may be reflective of targets' experience, we propose that predictions made based on these dimensions need further refinement. The theoretical and practical significance of these findings are discussed in relation to how workplace ostracism is typically studied in the literature.